Celts, Romans, Britons: classical and Celtic influence in the construction of British identities - Kaminski-Jones, Francesca; Kaminski-Jones, Rhys (Classical presences, 2020)
This work investigates the ways in which ideas associated with the Celtic and the Classical have been used to construct identities (national/ethnic/regional etc.) in Britain, from the period of the Roman conquest to the present day.